1997
DOI: 10.1021/la961027s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Fate of Nitrogen Functionality in Carbonaceous Materials during Pyrolysis and Combustion Using X-ray Absorption Near Edge Structure Spectroscopy

Abstract: X-ray absorption near edge structure (XANES) was used to investigate the fate of nitrogen functional groups in carbons derived from acridine, carbazole, and polyacrylonitrile during carbonization. Acenaphthylene and poly(vinyldene chloride) carbons with nitrogen incorporation by ammonia treatment at elevated temperatures were also studied. In general, the nitrogen XANES data provided more detail than the corresponding X-ray photoelectron spectroscopy (XPS) results and confirm the overall picture obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
75
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 24 publications
14
75
1
Order By: Relevance
“…3 Pyrolysis studies on model compounds indicated that under mild conditions pyrrolic nitrogen was converted into pyridinic nitrogen during condensation of the carbon matrix, and pyridones, protonated pyridinic nitrogen and pyridinic nitrogen oxides were also converted to pyridinic nitrogen. 4,14 In the condensation process, nitrogen is incorporated in the graphene sheets. It was concluded that under severe pyrolysis conditions (1 h at 1000°C) all nitrogen was present as either pyridinic nitrogen at the edge of the graphene sheets or as 'quaternary' nitrogen in the interior of these sheets.…”
Section: Discussionmentioning
confidence: 99%
“…3 Pyrolysis studies on model compounds indicated that under mild conditions pyrrolic nitrogen was converted into pyridinic nitrogen during condensation of the carbon matrix, and pyridones, protonated pyridinic nitrogen and pyridinic nitrogen oxides were also converted to pyridinic nitrogen. 4,14 In the condensation process, nitrogen is incorporated in the graphene sheets. It was concluded that under severe pyrolysis conditions (1 h at 1000°C) all nitrogen was present as either pyridinic nitrogen at the edge of the graphene sheets or as 'quaternary' nitrogen in the interior of these sheets.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Pyrrolic N atoms are bonded to one H atom and two C atoms in a non-aromatic or partially aromatic ring, with or without oxygen-containing substituents. (ii) Aromatic pyridinic rings contain N atoms in addition to oxygen-containing substituents (e.g., hydrated pyridinic rings, pyridone and pyridine carboxylic acids; defined by Mitra-Kirtley et al, 1993;Zhu et al, 1997;Vairavamurthy and Wang, 2002;Schnadt et al, 2003). Oxygencontaining substituents, such as hydroxyl groups, may provide chemically active sites for ring opening and subsequent elimination of N org (Katritzky et al, 1997;Siskin and Katritzky, 2000).…”
Section: Sub-peak N-5: Pyrrolic and Pyridinic Rings With Or Without Omentioning
confidence: 99%
“…(iii) Amine and amide moieties may be present in less mature coals and kerogens (Kelemen et al, 2006). Within the accuracy of XPS measurements, pyridone nitrogen cannot be distinguished from pyrrolic nitrogen (Zhu et al, 1997). Similar to pyridinic nitrogen, these reactive nitrogen species are primarily located along the edge of condensed and partially aromatic systems.…”
Section: Sub-peak N-5: Pyrrolic and Pyridinic Rings With Or Without Omentioning
confidence: 99%
“…%-i.e., BCN and BC 2 N compositions, respectively-is ascribed here to pyridone-like environments. 44 We observe that the N1s core-level edge of the BC x N-(a) coatings is comparable to h-BN for low C contents (10 at. %).…”
Section: B Carbon and Nitrogen 1s Core-level Edgementioning
confidence: 65%